2015
DOI: 10.1039/c5ra04162g
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of ZnO nanostructures: role of acetate (COOH) and nitrate (NO3) ligand donors from zinc salt precursors in synthesis and morphology dependent photocatalytic properties

Abstract: We investigated how the presence of one anion effects the overall ZnO growth in the presence of another anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…The development of various morphologies for Mn 2 O 3 has been investigated by different synthetic methodologies as a function of salt concentration, pH of the medium, solvent types, templates, and reaction temperature. There are examples of precursor dependent morphology evolution in case of ZnO, CdS, Cu 2 S and CdSe . Similar studies for the manganese‐based oxides are not reported to the best of our knowledge.…”
Section: Introductionsupporting
confidence: 66%
“…The development of various morphologies for Mn 2 O 3 has been investigated by different synthetic methodologies as a function of salt concentration, pH of the medium, solvent types, templates, and reaction temperature. There are examples of precursor dependent morphology evolution in case of ZnO, CdS, Cu 2 S and CdSe . Similar studies for the manganese‐based oxides are not reported to the best of our knowledge.…”
Section: Introductionsupporting
confidence: 66%
“…Various morphologies of Cu-CuO/ZnO were also formed as the generated nuclei were surrounded by CH 3 COO − ions. This was followed by further structural evolution upon decomposition of the CH 3 COO − ions to give CO 2 [11]. It can also be observed that ZnO NPs grow on the surface of the Cu-CuO rods.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 95%
“…As expected, the XRD pattern of Cu-CuO/ZnO contained peaks corresponding to Cu, CuO, and ZnO nanomaterials. More specifically, intense sharp peaks (as indicated by *) at 43.35° (111), 50.49° (200), and 74.08° (220), suggest the formation of crystalline Cu NPs [32], while peaks at 31.76° 100 [11]. In this case, the presence of ZnO reduced the crystallinity of CuO in the Cu-CuO/ZnO composite.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 95%
See 2 more Smart Citations